Jawabanmu

Jawaban paling cerdas!
2014-04-22T17:24:28+07:00
F(x) = 2x²+ 3x
lim      f(x+h) - f(x)  = lim      2(x+h)² +3(x + h) - (2x² + 3x)
h⇒0          h            h⇒0                  h

                           = lim      2(x² + 2xh +h²) +3x + 3h - 2x² - 3x
                              h⇒0                  h
                           = lim      2x² + 4xh + 2h² + 3h - 2x²
                              h⇒0                  h
                           = lim      4xh + 2h² + 3h
                              h⇒0                  h
                           = lim     h(4x + 2h + 3)
                              h⇒0                  h
                          = lim      (4x + 2h + 3
                             h⇒0  
                          = 4x + 3